2008
DOI: 10.2106/jbjs.g.00292
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells from Human Fat as Cellular Delivery Vehicles in an Athymic Rat Posterolateral Spine Fusion Model

Abstract: Adipose-derived stem cells show promise as gene transduction targets for inducing bone formation to enhance spinal fusion in biologically stringent environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 47 publications
3
87
0
Order By: Relevance
“…It is notable that animals in the rhBMP-2, Grafton 1 , and DBX 1 groups performed similarly to other studies utilizing the same doses of these products. 18,21,22,24 Because critics of rhBMP-2 use are concerned about the host inflammatory response demonstrated clinically in the cervical spine and lumbar interbody fusions, 10,11,16,17,34 TrioMatrix 1 was qualitatively and quantitatively evaluated in comparison to rhBMP-2 in a novel MR imaging protocol. Assessment 7 days after surgery demonstrated that the formation of an inflammatory response/fluid collection consistent with that described clinically after the use of rhBMP-2 was avoided with the use of TrioMatrix 1 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is notable that animals in the rhBMP-2, Grafton 1 , and DBX 1 groups performed similarly to other studies utilizing the same doses of these products. 18,21,22,24 Because critics of rhBMP-2 use are concerned about the host inflammatory response demonstrated clinically in the cervical spine and lumbar interbody fusions, 10,11,16,17,34 TrioMatrix 1 was qualitatively and quantitatively evaluated in comparison to rhBMP-2 in a novel MR imaging protocol. Assessment 7 days after surgery demonstrated that the formation of an inflammatory response/fluid collection consistent with that described clinically after the use of rhBMP-2 was avoided with the use of TrioMatrix 1 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by other studies that suggest that a local BMP threshold exists, below which no bone formation is seen. 24,49 The delivery of growth factors on a nanocrystalline scaffold, such as that which TrioMatrix 1 provides, may lead to the consistent and robust bone fusion that is not seen with conventional products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations